Analisis Location Quotient (LQ) Tanaman Cabai Besar (Capsicum annuum L.) di Provinsi Sumatera Utara - Brama Caridio Subambhi; Siti Mardiana; Faoeza Hafiz Saragih (Universitas Medan Area, 2020)
North Sumatra Province is a province that has a potential horticulture sector, which is a large chili plant, which is a long-term development program for 2016-2045, which was delivered at the Agricultural Development Planning Consultation (Musrenbangtan). Commodities priority becomes the main focus is the development of horticultural commodities chili, onion and garlic. This can be seen in the data from the Central Statistics Agency (BPS) of North Sumatra Province. The purpose of this study is to find out which regency is the base for large chili plants in North Sumatra Province. The analytical method used is, Location Quotient (LQ) Analysis with the data used in this study is secondary data. The planting area of large chilli plants and the production of large chili plants during the last ten years from 2007 to 2016. The results of the Location Quotient (LQ) Analysis show that the sector of the base for large chilli planting area has 5 highest districts, namely, Batu-Bara Regency, Phak-paak Bharat Regency, Dairi Regency, Humbang Hasundutan Regency, North Padang Lawas Regency. there are 5 highest chilli production base sectors, namely. District of Phak-pak Bharat, Batu Bara Regency, Mandailing Natal District, Langkat Regency and Nias Regency.